(untitled) (Global Journal of Management and Business Research, 2020)
The general objective of this study was to analyze the role of transformational leadership on the implementation of a national government multi-agency projectprogram in Kenya. The specific objectiveswereto examine the role of idealized influence andinspirational motivationand themoderating role of the legal framework on the implementation of digital literacy programs in Kenya. A descriptive and explorative research design was adopted as well asa positivism research philosophy.